Stainless steel 316L as bipolar plate material in proton exchange membrane water electrolyzer: The influence of potential and temperature on dissolution stability - Fiedler, Lena; Ma, Tien Ching; Fritsch, Birk; Dierner, Martin; Hoffmeister, Darius; Rubach, Carmen; Will, Johannes; Przybilla, Thomas; Spiecker, Erdmann; Dworschak, Dominik; Mayrhofer, Karl J.J.; Hutzler, Andreas (Materials Today Sustainability, 2025)
Stainless steel is a possible candidate for replacing titanium-based bipolar plates to reduce the cost of proton exchange membrane water electrolyzers. However, stainless steel is suspected to dissolve which could harm the system. Herein, we investigate the influence of applied potentials and temperatures on the dissolution stability of stainless steel (316L) in deionized (DI) water (pH ≈ 7) and highly diluted H2SO4 (pH ≈ 3) utilizing a scanning flow cell coupled on-line to an inductively coupled plasma mass spectrometer (SFC-ICP-MS). In H2SO4, the applied potentials critically influence the dissolution rates of 316L. Detrimental dissolution is observed at the open circuit potential, whereas dissolution is minimal in a potential window between 0.76 and 0.96 V. Temperature enhances the dissolution of 316L, especially due to a reduced stability of Cr. In DI water, the stability of 316L remains widely independent of potential and temperature, with dissolution rates remaining at an overall low level. Complementary scanning- and transmission electron microscopy reveal corrosion phenomena after electrochemical measurements in pH 3. Our results provide insights into factors influencing the stability of 316L and emphasize the importance of testing conditions that accurately mimic real-operations.
CRIS-Team Scopus Importer:2025-07-04
Keywords: Bipolar plates; Corrosion; DI water; H; Stainless steel; Water splitting